2016
DOI: 10.1016/j.addbeh.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-cigarette use by individuals in treatment for substance abuse: A survey of 24 treatment centers in the United States

Abstract: Prevalence and reasons for using electronic cigarettes (e-cigarettes) was examined among patients enrolled in 24 substance abuse treatment centers in the United States (N=1,113). Prevalence of e-cigarette use was assessed for the full sample. Bivariate analyses and multivariate logistic regression were used to identify characteristics associated with e-cigarette use among current cigarette smokers (the majority of e-cigarette users). Overall 55.5% of the sample reported lifetime use of e-cigarettes, and 30.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…These latter results were similar to those from a prior study of 1127 individuals from 24 substance abuse treatment centers that daily EC users were more likely to be on methadone maintenance and to be former cigarette smokers, and the majority of daily EC users were current cigarette smokers. 16 Both the results of this earlier study and the current analysis suggest that some individuals successfully switched from combustible cigarette use to EC use, but that switching might require daily EC use (i.e., persistent nicotine use) to maintain smoking abstinence. Alternatively, these individuals might reflect a subpopulation with a particularly strong motivation to stop smoking or who have lower nicotine dependence Third, we found that past-30-day EC users were more likely to report psychiatric symptoms compared with non-users.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These latter results were similar to those from a prior study of 1127 individuals from 24 substance abuse treatment centers that daily EC users were more likely to be on methadone maintenance and to be former cigarette smokers, and the majority of daily EC users were current cigarette smokers. 16 Both the results of this earlier study and the current analysis suggest that some individuals successfully switched from combustible cigarette use to EC use, but that switching might require daily EC use (i.e., persistent nicotine use) to maintain smoking abstinence. Alternatively, these individuals might reflect a subpopulation with a particularly strong motivation to stop smoking or who have lower nicotine dependence Third, we found that past-30-day EC users were more likely to report psychiatric symptoms compared with non-users.…”
Section: Discussionmentioning
confidence: 61%
“…Nonetheless, we note similarities between our patient population and others with OUD that have been previously studied. 16,23,25 Second, the cross-sectional data in the current analysis prevented examination of daily changes in smoking and EC use over time. Additional investigations utilizing longitudinal and experimental designs are needed to evaluate the impact of ECbased interventions on smoking cessation in people with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally problematic, approximately 30% of individuals in substance use treatment report current use of e-cigs [41]. Research indicates that targeting both smoking cessation and alcohol use in treatment results in better substance use outcomes [42] likely as a result of the mutually reinforcing properties of alcohol use and nicotine.…”
Section: Negative Outcomes Of Combined E-cig and Alcohol Usementioning
confidence: 99%
“…Patterns of use of other nicotine products with VLNC in an open market, including by individuals abusing other substances [8] or challenged by mental illness, could help to assess what might be wrought by a mandatory VLNC policy [18]. Applying simplified models of what will happen in complex systems often goes wrong [19].…”
Section: The Simplified Theoretical World Of Mandatory Nicotine Redumentioning
confidence: 99%
“…Compliance with VLNC by healthy, well-paid volunteers sheds light upon challenges smokers might face, even if greater challenges could befall mentally ill, alcohol-abusing smokers [6,8].…”
mentioning
confidence: 99%